Implementation of Mind Map-Cooperative Learning Model to Improve Learning Outcomes in Objects and Its Properties Material of Fifth Grade Students at MI Islamiyah Purwojati Mojokerto - Pramunita, Rian Ningsih (Indonesian Journal of Science Learning (IJSL), 2021)
This study aims to improve student learning outcomes in science subjects of objects and their properties at MI Islamiyah Purwojati Mojokerto through the implementation of a mind map type-cooperative learning model. This research was conducted using Kurt Lewin’s model consisting of 2 cycles with each cycle has 4 stages. The study was conducted at MI Islamiyah Purwojati Mojokerto with a sample of 29 Fifth Grade students. Data collection techniques through observation, interviews, tests, and documentation. The results are the implementation of mind map type-cooperative learning model can increase teacher activity from 71 points (enough) in the first cycle to 91 points (very good) in the second cycle, student activities from 72 points (enough) in the first cycle to 97 points (very good) in cycle II. Student learning outcomes increased from 13.8% (very less) in the pre-cycle, 51.8% (less) in the first cycle, and 82.8% (good) in the second cycle. Based on the results on teacher activities, student activities and learning outcomes, it can be concluded that there was a better increase in each cycle.